2020
DOI: 10.1002/ctm2.244
|View full text |Cite
|
Sign up to set email alerts
|

Definition of erythroid cell‐positive blood transcriptome phenotypes associated with severe respiratory syncytial virus infection

Abstract: Immune determinants of respiratory syncytial virus (RSV) disease severity remain ill-defined. We conducted a meta-analysis of six public RSV blood transcriptome datasets. Severe patients molecular phenotypes presented traits associated with immunosuppressive states and extramedullary erythropoiesis signatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…Recent studies revealed that extramedullary erythropoiesis and EPC expansion may also be a part of the inflammatory response [ 128 , 129 , 130 ]. A recent analysis of blood transcriptome revealed that the signature of immature erythroid cells is also associated with severe respiratory syncytial virus (RSV) infection, pharmacological immunosuppression, and late-stage cancer [ 131 ].…”
Section: Expansion Of Erythroid Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that extramedullary erythropoiesis and EPC expansion may also be a part of the inflammatory response [ 128 , 129 , 130 ]. A recent analysis of blood transcriptome revealed that the signature of immature erythroid cells is also associated with severe respiratory syncytial virus (RSV) infection, pharmacological immunosuppression, and late-stage cancer [ 131 ].…”
Section: Expansion Of Erythroid Progenitor Cellsmentioning
confidence: 99%
“…In tumor-bearing mice, EPCs expand during tumor progression in many extramedullary organs ( Table 6 ), predominantly the spleen, liver, and peripheral blood, as well as infiltrate tumors [ 41 , 43 , 62 ]. In humans, EPCs were detected in the spleen, TME, and peripheral blood of cancer patients [ 41 , 62 , 123 , 131 ]. In general, anemia severity correlates with the frequency of EPCs [ 41 ].…”
Section: Expansion Of Erythroid Progenitor Cellsmentioning
confidence: 99%
“…We have since resumed our efforts toward developing such resources, using new applications such as R/Shiny that support the interactive generation of fingerprint plots. These applications have been made available as ad hoc supplements to different publications [reference dataset for module construction: https://drinchai.shinyapps.io/dc\_gen3\_module\_analysis/ ( Altman et al , 2020 ); meta-analysis of respiratory syncytial virus blood transcriptome data: https://drinchai.shinyapps.io/RSV\_Meta\_Module\_analysis/ ( Rinchai et al , 2020a ); development of targeted Covid-19 blood transcript panels: https://drinchai.shinyapps.io/COVID\_19\_project/ ( Rinchai et al , 2020b )]. Together with making the BloodGen3Module R package available and depositing the scripts via GitHub: https://github.com/Drinchai/BloodGen3Module/ , we hope that deploying these applications via R/Shiny will guarantee their availability over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transcriptome profiling involves measuring circulating leukocyte RNA abundance on a global scale. This approach has been used extensively to identify the transcriptomic changes associated with pathologies such as infection, autoimmunity, neurodegeneration, cardiovascular diseases and cancer ( Bhardwaj et al , 2020 ; Chaussabel, 2015 ; Freedman et al , 2010 ; Karsten et al , 2011 ; Mejias et al , 2014 ; Pascual et al , 2010 ; Rinchai et al , 2020a ). It has also been employed to monitor responses to vaccines and therapeutic agents ( Nakaya and Pulendran, 2015 ; Pascual et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse collections of omics-based experiments have the potential to help elucidate the immunology and genetics underlying the heterogeneity of the pathogenesis of sepsis [ 12 , 13 ]. In that regard, reductionist approaches have been used to successfully identify putatively novel genes/functions [ 14 , 15 , 16 , 17 ] and perform system-level reanalysis [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%